New taxa of Tanyderidae (Diptera) from Eocene Baltic amber - Krzeminski, Wiesław; Krzeminska, Ewa; Kania, Iwona; Ross, Andrew J. (Zootaxa, 2013)
Macrochile hornei sp. nov. from Baltic amber (Upper Eocene) is described and illustrated. Podemacrochile gen. nov. is described with Podemacrochile baltica (Podenas, 1997) as type species. A key to the genera and species of Tanyderidae known from Baltic amber is presented.